Finite element analysis of the temperature uncertainty during spark plasma sintering: Influence of the experimental procedure. Issue 17 (1st December 2017) - Achenani, Youssef; Saâdaoui, Malika; Cheddadi, Abdelkhalek; Fantozzi, Gilbert
Abstract: Finite element analysis of the dispersion of the dwell temperature during spark plasma sintering (SPS) was performed considering two error sources: misalignment of the axial pyrometer and a shift of the die relatively to the sample. Both error sources induce comparable temperature deviations. In the case of a pyrometer misalignment, these deviations are sensitive to the sample diameter. The errors have no significant effect on the radial temperature gradient within the sample; however, they modify the level of temperature which can be considerably deviated from the set point in the case of cumulative errors. Graphical abstract: Highlights: Temperature measurements during SPS sintering presented a noticeable dispersion. Misalignment of the axial pyrometer was identified as a potential error source. A shift of the die relatively to the sample is also a potential error source. A deviation of the sample temperature from the set point was induced. Cumulative errors amplify this deviation and induce significant axial gradients.